Preparation of sponge-reinforced silica aerogels from tetraethoxysilane and methyltrimethoxysilane for oil/water separation. (5th April 2018) - Li, Ming; Jiang, Hongyi; Xu, Dong
Abstract: Polyurethane sponge-reinforced silica aerogels based on tetraethoxysilane (TEOS) and methyltrimethoxysilane (MTMS) were fabricated by a facile method through sol-gel reaction followed by ambient pressure drying. In sponge-reinforced silica aerogels, nanoporous aerogel aggregates fill in the pores of polyurethane sponge. The sponge-reinforced aerogels are hydrophobic and oleophilic and show extremely high absorption for machine oil (10.6 g g −1 for TEOS-based aerogel and 9.2 g g −1 for MTMS-based aerogel). In addition, the sponge-reinforced aerogel composites exhibit notable improvements with regards to mechanical properties. The compressive strength was enhanced obviously up to about 349 KPa for TEOS-based aerogel and 60 KPa for MTMS-based aerogel. Specially, sponge-reinforced silica aerogels based on MTMS drastically shrank upon loading and then recovered to the original size when unloaded. The property differences of the sponge-reinforced silica aerogels caused by the two precursors were discussed in terms of morphologies, pore size distributions and chemical structure.